Tension Causes Unfolding of Intracellular Vimentin Intermediate Filaments. Issue 11 (1st November 2020) - Fleissner, Frederik; Kumar, Sachin; Klein, Noreen; Wirth, Daniel; Dhiman, Ravi; Schneider, Dirk; Bonn, Mischa; Parekh, Sapun H.
Abstract: Intermediate filament (IF) proteins are a class of proteins that constitute different filamentous structures in mammalian cells. As such, IF proteins are part of the load‐bearing cytoskeleton and support the nuclear envelope. Molecular dynamics simulations show that IF proteins undergo secondary structural changes to compensate mechanical loads, which is confirmed by experimental in vitro studies on IF hydrogels. However, the structural response of intracellular IF to mechanical load is yet to be elucidated in cellulo. Here, in situ nonlinear Raman imaging combined with multivariate data analysis is used to quantify the intracellular secondary structure of the IF cytoskeletal protein vimentin under different states of cellular tension. It is found that cells under native cellular tension contain more unfolded vimentin than chemically or physically relaxed specimens. This indicates that the unfolding of IF proteins occurs intracellularly when sufficient forces are applied, suggesting that IF structures act as local force sensors in the cell to mark locations under large mechanical tension. Abstract : Vimentin intermediate filaments are part of the load‐bearing cytoskeleton. Using in situ nonlinear Raman imaging combined with multivariate data analysis, the intracellular secondary structure of vimentin under different states of cellular tension is quantified. Cells under native tension contain more unfolded vimentin than chemically or physically relaxed cells.